2018
DOI: 10.1080/09537104.2018.1453058
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four methods to assess high-on platelet reactivity under P2Y12 receptor inhibitor

Abstract: P2Y12 receptor inhibitors are antiplatelet agents commonly prescribed in the treatment of coronary artery disease. Their efficacy can be limited by high on-treatment platelet reactivity (HPR), which can be evaluated by different biological assays. Most commonly, HPR is evaluated by flow cytometric vasodilator-stimulated phosphoprotein-phosphorylation (VASP-P) assay, which can be time consuming. To evaluate the potential interest of novel technologies, we compared four different assays. Ninety patients receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…The results are reported as a percentage of maximum platelet aggregation. High platelet reactivity was defined as maximum platelet aggregation > 59% (LTA 20 μM/L) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results are reported as a percentage of maximum platelet aggregation. High platelet reactivity was defined as maximum platelet aggregation > 59% (LTA 20 μM/L) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Multiplate test has been shown to best reflect the in vivo plasma concentrations of ticagrelor and its active metabolite compared to other tests (VerifyNow and VASP) [21]. Other studies have shown Multiplate, VASP and platelet function analyser tests to have moderate agreement regarding the classification of patients as responders to P 2 Y 12 inhibition [22]. Therefore, the Multiplate test is a valid method of evaluating platelet response to antiplatelet therapy in our patient cohort.…”
Section: Discussionmentioning
confidence: 92%
“…Comparisons of various currently used PFTs have been extensively studied. Variations and poor concordances of different PFTs were demonstrated [ 17 , 35 ]. Before adopting a new PFT to be applied in clinics, correlation analysis between the new one and the gold standard method is generally performed.…”
Section: Discussionmentioning
confidence: 99%
“…LTA was developed in early 1960s, and has still been considered as a classical gold method to evaluate platelet reactivity [14]. However, LTA is characterized with lacking standardization, time-consuming, plasma based test, complicated sample preparation and professional expertise requirement, which limits its clinical routine application [15][16][17]. While the point-of-care test, TEGpm, meets the optimal PFT demands for clinical practice due to easy to perform, being available at bedside with flexible time and whole blood sample for testing.…”
Section: Introductionmentioning
confidence: 99%